Federalismo e políticas públicas de saúde: a institucionalidade da regionalização e da Comissão Intergestores Bipartite no Estado do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The present thesis aims to analyze the institutional framework of the regionalization of health policy in the State of Paraná and the Bipartite Interagency Commission (CIB/PR), from 2011 to 2015, starting from the discussion of federalism and public health policies. It is a documentary research related to the analysis of the rules of the Paraná State Interagency Committee, the Regionalization Master Plan and the State Health Plan, as well as the main federal and state regulations related to regionalization and the CIB/PR. The technique adopted to carry out the work is a content analysis. The theoretical reference for the analysis of the regionalization of health policy was the neo-institutionalism, specific, on the slope of historical institutionalism. The thesis it is divided into four chapters. The first chapter analyze the recognition process of the fundamental right to health, in the international ambit and in the internal ambit, in special, when its characterization as utility right and as fundamental asset. In the second chapter is analyzed the federalism and the publics health policies, to demonstrate the implications existing between both. In the third, a normative trajectory of the health policy is made to demonstrate the way traveled after the Constitution of 1988 until the regionalization, has as referential the Decree n° 7.508/2011. In the fourth chapter realizes the analysis of the categorical from categories pre-defined and of the records units taking into account the informations contained in the minutes of ordinary meetings of the BIC/PR realized in the period from 2011 to 1015, for analyzed the dimension of the institutionality. The results of the search demonstrate that the institutionality of regionalization and the institutionality of the Bipartite Interagency Committee (BIC/PR) it is classified as advanced, having contributed for the implantation of the health care networks and, therefore, of guarantees of the right to health.
Keywords: Federalismo; Políticas Públicas.; Regionalização.; Gestores de saúde; Direito à saúde.; Federalism; Public policy.; Regional Health Planning; Health Manager; Right to health; CNPQ::CIENCIAS SOCIAIS APLICADAS